Regulating Virtual Land Sales in Indonesia's Metaverse: Mengatur Penjualan Tanah Virtual di Metaverse Indonesia - Safitri, Baiq Riska Anggi; Arba, Arba; Wagian, Diangsa (Indonesian Journal of Law and Economics Review, 2024)
<div class="min-h-[20px] text-message flex flex-col items-start gap-3 whitespace-pre-wrap break-words [.text-message+&]:mt-5 overflow-x-auto" data-message-author-role="assistant" data-message-id="d1727dee-033f-4fe3-9e9f-1f02f6f73e31"> This study explores the legal challenges and implications of virtual land sales through the metaverse in the context of Indonesia's digital era 5.0, focusing on consumer protection and the prevention of digital crimes. The primary aim is to analyze the legal framework governing these transactions and assess their conformity with the principles of valid contracts under Indonesian civil law. Employing a normative research methodology, the study evaluates existing regulations and legal literature to understand the current legal landscape. The findings reveal a lack of specific legislation in Indonesia regarding virtual land transactions in the metaverse, categorizing them under general electronic transactions governed by the Electronic Information and Transactions Law. Despite this, these transactions generally meet the legal requirements of a valid contract in Indonesian civil law, such as mutual consent, competency, a specific object, and a lawful cause. However, the study underscores the need for specific regulations to provide legal clarity and enhanced protection for parties involved in virtual land sales, considering the unique and virtual nature of the transaction objects. The research concludes with a call for international collaboration to contribute to the development of a balanced and contemporary global legal framework for metaverse transactions. Highlights: Absence of Specific Legislation: Current Indonesian laws do not specifically address virtual land sales in the metaverse, creating legal ambiguity. Electronic Transaction Classification: Virtual land sales are generally governed by Indonesia's Electronic Information and Transactions Law, aligning them with other electronic transactions. Need for Enhanced Legal Protection: Given the unique nature of virtual transactions, there is a significant need for specific regulations to ensure legal clarity and protect the rights of parties involved. Keywords: Metaverse, Virtual Land Sales, Indonesian Law, Electronic Transactions, Legal Framework